Customer Journey in B2B Services : Understanding the Formation of Customer Experience in Insurance Services - Havaste, Antonia (fi=Turun yliopisto|en=University of Turku|, 2018)
Creating superior customer experiences is undoubtedly a key strategic initiative in today's highly competed service market. Due to the increasing competition in the field of B2B services, organizations have started applying experience management strategies to overcome the problems of digitalization, standardization and disadvantages in pricing. Especially in the field of complex B2B financial services, such as insurance and banking, delivering a great customer experience is found to strengthen loyalty and customer satisfaction and offer an effective source of differentiation. To date, experiences have been studied mostly in the context of experimental consumer services. Thus, this study represents one of the few ones conducted in the field of B2B services, aiming to study how B2B customer experience emerges in the context of insurance services. The research question is divided in three sub-questions: 1. How B2B customer journey emerges as a constellation of various touchpoints in insurance services 2. Which elements critically affect the B2B customer experience in the different stages of the customer journey and 3. What is the preferred B2B customer experience in insurance services. The literature review of the study consists of the currently evolving research on B2B customer experience, customer journey and touchpoints, experience elements and experience goals. Moreover, B2B insurance services and their special characteristics are presented and discussed. The empirical data is collected by semi-structured thematic interviews of 10 B2B customers of Finnish insurance companies. The study applies a phenomenological methodology, which empathizes the interviewees' individual interpretations of their experiences in collecting and analyzing the data and interpreting the findings. The findings of the study indicate that B2B customer experience emerges as result when customer proceeds through the customer journey across various touchpoints. Moreover, multiple context-related elements, and how customers mentally evaluate the quality of the experience by contrasting it with their own goals, essentially affect the resulting holistic customer experience. Thus, the study combines the different theoretical concepts of customer experience, which have been studied mainly as separate constructs. By reflecting the framework with the findings, a detailed B2B customer experience journey map of insurance services is presented.